2016
DOI: 10.2166/wst.2016.442
|View full text |Cite
|
Sign up to set email alerts
|

An integrated model for simulating and diagnosing the water quality based on the system dynamics and Bayesian network

Abstract: An integrated model for simulating and diagnosing water quality based on the system dynamics and Bayesian network (BN) is presented in the paper. The research aims to connect water monitoring downstream with outlet management upstream in order to present an efficiency outlet management strategy. The integrated model was built from two components: the system dynamics were used to simulate the water quality and the BN was applied to diagnose the reason for water quality deterioration according to the water quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
7
0
2
Order By: Relevance
“…Existing studies considered the combination of a probabilistic evaluation performed by BN with one deterministic approach, like SDMs or ABM (Bertone et al, 2016a;Phan et al, 2016;Wang et al, 2016;Pope and Gimblett, 2015;Kocabas and Dragicevic, 2013). Advantages of this "hybridization" include the capacity of dealing with a high degree of uncertainty, the use of feedback loops and the integration of quantitative and qualitative data.…”
Section: Multi-risk Criteria Fulfilmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies considered the combination of a probabilistic evaluation performed by BN with one deterministic approach, like SDMs or ABM (Bertone et al, 2016a;Phan et al, 2016;Wang et al, 2016;Pope and Gimblett, 2015;Kocabas and Dragicevic, 2013). Advantages of this "hybridization" include the capacity of dealing with a high degree of uncertainty, the use of feedback loops and the integration of quantitative and qualitative data.…”
Section: Multi-risk Criteria Fulfilmentmentioning
confidence: 99%
“…Moreover, Wang et al (2016), Pope and Gimblett (2015) and Kocabas and Dragicevic (2013) performed a spatial analysis together with discrete temporal representation, looking at changes of systems variables and creating output maps. In addition to that, Pope and Gimblett (2015) also extended the analysis to future scenarios of climate change, assessing water scarcity impacts across different sectors (i.e.…”
Section: Multi-risk Criteria Fulfilmentmentioning
confidence: 99%
“…', through conducting trade-off analysis to find out the most optimal management options with/without exploring different scenarios (e.g., [17,137]). Only 27% of reviewed studies developed BNs for predictive modelling only, meaning that these studies just focused on understanding the systems without exploring any scenarios or management measures (e.g., [36,60,141]).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…They have complementary advantages and disadvantages, and thus it has been suggested to use both models to complement each other for a comprehensive water management assessment (Sušnik et al 2013). However, to the authors' knowledge, confirmed by recent reviews (Phan et al 2016b), there have been very limited attempts to combine these two modelling approaches (Phan et al 2016a;Wang et al 2016), in particular no attempts of using BN knowledge to develop a SD that can deal with missing data and uncertainty.…”
Section: Extreme Events and Water Quality: Modelling Challengesmentioning
confidence: 99%